A joining of traditional and e-commerce approaches for transferring environmental technologies from laboratory to market. (20th February 2004) - Camden, Michael; Joltes, Tracee
This paper will explore the Robert C. Byrd National Technology Transfer Center's (NTTC) current, traditional approach to technology transfer, relating to technologies developed by the US Environmental Protection Agency (EPA). It will present insight into the future of environmental technology transfer at NTTC including a novel approach that merges e-commerce with successful aspects from traditional methods, and the steps involved in NTTC's current EPA technology transfer process. An outline of NTTC's plan for the future of environmental technology transfer is also included. This plan will make use of various e-commerce initiatives to be employed by NTTC, including a knowledge-management portal and online technology demonstrations. Finally, this paper will show how NTTC intends to merge a traditional approach to technology transfer with the outlined e-commerce initiatives to better facilitate the transfer of EPA technologies from the laboratory to the market.